Effect of fertilizer type on wheat yield and soil fertility content (Mongolian Journal of Agricultural Sciences, 2024)
According to the researchers, soil erosion in the cultivation center area is 61.1-81.3%. That the yield of moderately and severely eroded areas has decreased by 50-80%, the grain ripens late, and the quality and standards of the product have not been met. Soil erosion and fertility degradation are causing disaster and destruction in agricultural areas. Therefore, there is an urgent need to use fertilizers in the agricultural areas of our country. Fertilizers, minerals, nutrients, bacteria, and mineral-nutrient fertilizers used in our study were studied by soil layers at the same time, which is unique to the work of other researchers. According to the results of our research, wheat yield is 9.0-16.4 t/ha higher in all fertilized scenarios than in the unfertilized (control) scenario. The highest yield was obtained with Wacom fertilizer (42.6 t/ha). Fertilizer types increased by 0.18-0.95% in soil humus content compared to the control version. The highest increase was 1% in the version with mineral-nutrient type (BR-481) series fertilizers.